Some questions of the competency approach in teaching foreign (Korean) language in Kazakhstan - Тен, Ю. П.; Кыдырбaев Б. М. (Journal of Oriental Studies, 2017)
The article deals with the competence-based approach in the teaching of a foreign language (Korean) language in Kazakhstan. The new requirements of the labor market pose new competence in the teaching of Korean language. The key ones are interpersonal, intercultural, social and the civil jurisdiction. The use of IT technologies will create conditions similar to the language environment.